Application of Interactive Learning Multimedia Based on Microsoft Powerpoint in Improving Mathematics Learning Outcomes - Baharuddin, Baharuddin; Asmaun, Asmaun (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
Microsoft interactive learning media Powerpoint In elementary schools, mathematics subjects still need to be the focus of teachers' attention as an effort to improve low learning outcomes, so this research aims to improve learning outcomes. fifth grade students through the application of interactive learning multimedia . The approach used is a qualitative approach using the type of classroom action research (CAR). The focus of this study is two, namely the focus of the process and the focus of the results. The subjects of this study were researchers and 13 fifth grade students consisting of 6 males and 7 females. Data collection techniques used in this study were tests, observations, video recordings and documentation . The data analysis used is descriptive data analysis by grouping data on Teacher Aspects and Student Aspects. This study consists of 2 cycles and each cycle consists of 2 meetings . The results of the study indicate that the qualification of the interactive learning process based on Microsoft Powerpoint in cycles I and II are getting better . Along with that, students' understanding ability also increases in cycles I and II. The conclusion of this study is that the process of implementing interactive multimedia makes the learning atmosphere active and enjoyable. The changes in the learning process that have been described are able to encourage increased student learning outcomes